2018
DOI: 10.1016/j.bbrc.2018.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Stasimon/Tmem41b localizes to mitochondria-associated ER membranes and is essential for mouse embryonic development

Abstract: Stasimon (also known as Tmem41b) is an evolutionarily conserved transmembrane protein first identified for its contribution to motor system dysfunction in animal models of the childhood neurodegenerative disease spinal muscular atrophy (SMA). Stasimon was shown to be required for normal neurotransmission in the motor circuit of Drosophila larvae and proper development of motor axons in zebrafish embryos as well as to suppress analogous neuronal phenotypes in SMA models of these organisms. However, the subcellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 22 publications
(36 reference statements)
4
24
0
Order By: Relevance
“…On the basis of these phenotypic similarities, one immediate hypothesis is that TMEM41B and VMP1 function as a complex. Indeed, Morita and colleagues were able to isolate a VMP1/TMEM41B-containing co-complex in the presence of n-dodecyl-β-D-maltoside/cholesteryl hemisuccinate (DDM/CHS) [53], although such a complex was not observed in other detergents [54,55]. It remains an important future goal to establish whether TMEM41B’s function is dependent on its interaction with VMP1.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of these phenotypic similarities, one immediate hypothesis is that TMEM41B and VMP1 function as a complex. Indeed, Morita and colleagues were able to isolate a VMP1/TMEM41B-containing co-complex in the presence of n-dodecyl-β-D-maltoside/cholesteryl hemisuccinate (DDM/CHS) [53], although such a complex was not observed in other detergents [54,55]. It remains an important future goal to establish whether TMEM41B’s function is dependent on its interaction with VMP1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that Stasimon is an ER-resident, six-transmembrane-pass protein that is essential for mouse embryonic development (Van Alstyne et al, 2018b) and functions in autophagy (Moretti et al, 2018;Morita et al, 2018;Shoemaker et al, 2019). There have also been reports of autophagy dysregulation in SMA, but there is disagreement about whether this pathway is inhibited (Custer and Androphy, 2014;Periyakaruppiah et al, 2016;Rodriguez-Muela et al, 2018) or stimulated (Gonç alves et al, 2018;Piras et al, 2017) by SMN deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Stasimon is expressed at high levels in mouse neural tissues, and studies recently showed that it is expressed at point of contact between the endoplasmic reticulum (ER) and mitochondria. Over-expression of GFP-tagged Stasimon in HEK293T cells followed by immunoprecipitation identified α-COP as a Stasimon interacting protein [29]. This finding opens up the possibility that by expressing α-COP, we are impacting Stasimon function in a way that is beneficial to SMA mice, perhaps by enhancing its function at the interface between the ER and mitochondria.…”
Section: Discussionmentioning
confidence: 83%